The search phase of college choice as experienced by eleven prospective students visiting a Midwest College of Agriculture - Klein, Sandra (Kansas State University, 2011)
Each year higher education institutions seek to recruit and attract high school graduates to their institutions. Millions of high school seniors each year are in the midst of the college choice process, attempting to determine which institution is “right” for them. This study explored college choice factors important to high school seniors in the search phase of the college choice process. To carry out this study purposeful sampling was used to select 11 high school seniors participating in individually scheduled campus visits. An interview process was used to investigate what college choice factors were important to them when choosing a university/college. Student responses were ultimately categorized into six areas: interest in a specific major/program area, reputation, ideal distance from home, family interaction with institution, factors related to paying for college, and campus environment.
Keywords: College Choice; Education, Agricultural (0517); Higher Education (0745)